Federal Grand Jury Testimony and the Fifth Amendment - Merle L. Silverstein (Washington University Law Quarterly, 1960)
In recent years, the extensive employment of the fifth amendment privilege by various individuals associated with unpopular causes, resulting in the frustration of many important government inquiries, has encouraged bitter criticism of the amendment from various legal and lay sources. Nevertheless, it is safe to assume that “our old friend” is here to stay, and has become an integrated and essential part of our democratic way of life. The castigations of the critics and newspaper editorials to the contrary notwithstanding, the proper invocation of the self-incrimination privilege is not to be deemed inconsistent with good citizenship. The prospective grand jury witness and his attorney should therefore become closely familiar with the duties and obligations of such a witness, and the instances in which they may be legally superseded by privilege. This Article is concerned with increasing such familiarization.
Keywords: Grand jury; Self-incrimination